Assessment of Social Competence Perceived in Martial Arts and Tendency towards Sport Activities - Abdulkerim Çeviker; Gamze Deryahanoğlu; Osman Kusan (Journal of Educational Issues, 2024)
Considering that the socially perceived competence in athletes shall continue not only the tendency to the sport activities but also the mutual effects of showing more effort and participation in sport activities, our aim is to assess the perceived competence and tendency towards sport activities in martial arts athletes. The study is composed total of 220 athletes, 92 males and 128 females, in the branches of Kickboxing, Taekwondo, and Boxing. In the research, in order to determine the “Tendency towards Sports Activities” and the “Perceive Social Competence” levels of the athletes are used. The analysis of the data is performed utilizing SPSS 22.0 package program. In group comparisons, the Mann-Whitney U Test, Kruskal-Wallis Test are used. The analysis of the data is assessed at 95% confidence interval and p < 0.05 significance level. There are significant differences determined in perceived social competence, total score of tendency towards sports and emotion search sub dimension based on the genders of the athletes. Based on the branch variable of the athletes, in perceived social competence, general scale tendency towards sports, socializing sub dimension and emotion search sub dimension, significant differences are determined. As a result, it is concluded that they follow up-to-date sports regularly and this increases the social competence and sports tendency of the athletes; that Kickboxing athletes, the one who started the sport on their own will and male athletes have higher social competence and sport tendencies.